2013
DOI: 10.5395/rde.2013.38.3.141
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the level of salivary alpha amylase activity and pain severity in patients with symptomatic irreversible pulpitis

Abstract: ObjectivesAssessment of dental pain severity is very challenging in dentistry. Previous studies have suggested that elevated salivary alpha amylase may contribute to increased physical stresses. There is a close association between salivary alpha amylase and plasma norepinephrine under stressful physical conditions. The aim of this study was to evaluate the relationship between pain severity and salivary alpha amylase levels in patients with symptomatic irreversible pulpitis.Materials and MethodsThirty-six pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 24 publications
(24 reference statements)
4
20
2
1
Order By: Relevance
“…These results are similar to those reported previously by Shirasaki and Motamayel [4,5]. It has been reported that psychological stress activates the SAM system [6].…”
Section: Discussionsupporting
confidence: 83%
“…These results are similar to those reported previously by Shirasaki and Motamayel [4,5]. It has been reported that psychological stress activates the SAM system [6].…”
Section: Discussionsupporting
confidence: 83%
“…Multiple peer-reviewed studies have validated the application of sAA concentration as a noninvasive biomarker for both objective pain intensity and emotional status in a stressful environment. [3][4][5] This study did not find that sAA factors (both sAA concentration and sAA output rate) were related to either VAS or DAS score. These findings corroborate those of Sadi et al, 14 who also found no significant correlation between DAS and sAA factors.…”
Section: Das and Vasmentioning
confidence: 57%
“…3 In our study, sAA was used as a biomarker for sympathetic activity on account of the powerful role the autonomic nervous system plays in sAA secretion and the acceptance within the published literature of sAA as a sympathetic biomarker. 4,5,[12][13][14][15] The net result of sympathetic stimulation on the salivary glands is a thicker, protein-rich saliva, in contrast to the watery saliva produced by parasympathetic activity. Multiple peer-reviewed studies have validated the application of sAA concentration as a noninvasive biomarker for both objective pain intensity and emotional status in a stressful environment.…”
Section: Das and Vasmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, there has also been an interest in the assessment of stress biomarkers, such as salivary α‐amylase (sAA) and salivary cortisol, as surrogates for psychological stress in women with infertility . Within the broader literature, it is of great interest to note that sAA in particular has been associated both with psychosocial stress, including specific anxiety scores, such as the State–Trait Anxiety Inventory (STAI) score, and also physical stress/painful stimuli, with a strong correlation with the visual analogue scale (VAS) for pain . It is therefore evident that stress, anxiety and pain, along with their respective biomarkers, are intertwined …”
Section: Introductionmentioning
confidence: 99%